ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN DAN PENGUPAHAN KARYAWAN PADA PRAMUDI ANGKUTAN SISWA GRATIS DALAM UPAYA MENINGKATKAN EFEKTIVITAS PENGENDALIAN INTERN PERUSAHAAN - I Made Manik Dwijantara; Sang Ayu Putu Arie Indraswarawati; Ni Wayan Yuniasih (UNHI Press, 2021)
The payroll accounting system is an important component in accounting information. This system consists of a framework that is interconnected within a company which functions to inform cost data needed by interested parties in the company. The payroll accounting information system that has been implemented by PT. Damri Klungkung Branch and also to analyze the payroll accounting information system on the effectiveness of internal control. This type of research is descriptive qualitative research, which focuses on the payroll accounting information system at PT. Damri Klungkung Branch. Data analysis in this study begins with a description of the payroll accounting information activities, analyzing information, supporting documents, accounting records used, related functions, the network of procedures that make up the payroll and wage systems, and the effectiveness of internal controls. The results of the study found evidence that the Accounting Department is still responsible for paying employees' salaries and wages and is still responsible for supervising the filling of employee attendance lists and making a recap of employee attendance lists so that fraud is possible. Sound practices that are implemented to support the effectiveness of internal control are that the employees' basic salaries are paid by transferring the basic salaries to the account of each employee by the director and the pay slips are made in duplicate.